KENAKALAN REMAJA DI KALANGAN SANTRI PONDOK PESANTREN PUTRI AL-FATHIMIYYAH BAHRUL ULUM TAMBAKBERAS JOMBANG - Arizona, Vransiska Fami; Kebayantini, Ni Luh Nyoman; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study aims to analyze and explain the reasons for juvenile delinquency and the forms of violations that occur in Islamic boarding schools conducted by students of the Putri Al-Fathimiyyah Islamic Boarding School Bahrul Ulum Tambakberas Jombang. The approach used in this research is descriptive exploratory type and uses Robert K Merton theory analysis of Adaptation Typology. The results of the field research that have been found are that there are several reasons for students to commit violations namely because there are too many regulations, feeling bored and unable to control themselves and there is pressure from the family. Santri who have committed the violation will then be given sanctions in the form of a penalty set by the board or caretaker of the boarding school. Keywords: Juvenile Delinquency, Santri, Islamic Boarding School .